Lactobacillus paracasei BD5115-Derived 2-Hydroxy-3-Methylbutyric Acid Promotes Intestinal Epithelial Cells Proliferation by Upregulating the MYC Signaling Pathway - Qiao, Zhenyi; Wang, Xiaohua; Wang, Chaoyue; Han, Jin; Qi, Weiwei; Zhang, Huanchang; Liu, Zhenmin; You, Chunping (Frontiers in Nutrition, 2022)
Metabolites of probiotics that are beneficial to human health have been isolated from the intestinal tract and natural dairy products. However, many studies on probiotics and prebiotics are limited to the observation of human cohorts and animal phenotypes. The molecular mechanisms by which metabolites of probiotics regulate health are still need further exploration. In this work, we isolated a strain of Lactobacillus Paracasei from human milk samples. We numbered it as Lactobacillus Paracasei BD5115. The mouse model of high-fat diet confirmed that the metabolites of this strain also promotes intestinal epithelial cells (IECs) proliferation. Single-cell sequencing showed that a bZIP transcription factor MAFF was specifically expressed in some IECs. We found that MAFF interacted with MBP1 to regulate the expression of MYC. Analysis of the active components in BD5115 metabolites confirmed that 2-hydroxy-3-methylbutyric acid promotes the expression of the MYC gene. This promotes the proliferation of IECs. Our findings indicate that 2-hydroxy-3-methylbutyric acid regulate MYC gene expression mediated by MAFF/MBP1 interaction. This study not only screened a strain with promoted IECs proliferation, but also discovered a new signal pathway that regulates MYC gene expression.